Produksi Aluminium Sulfat dari Kaolin dan Asam Sulfat Dalam Reaktor Berpengaduk Menggunakan Proses Kering - Ismayanda, Muhammad Husin (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
Aluminium sulphate is form by reacting alumina which contains in kaolin with sulphuric acid solution in a stirred reactor. Reaction occurs in variance of different time and temperature. The result of reaction is paste aluminium which will be extracted about 3 times using hot aquadest and consentration of aluminum analized by titrimetric methode. Time, temperature and ratio of sulphuric acid and kaolin in reaction have a lot effect to conversion value result, while sulphuric acid concentration and speed of agitation are not too effected. Process condition which is about to be good is temperature 180 oC, reaction time 90 minutes, ratio of sulphuric acid and kaolin is 3:1, sulphuric acid concentration 65% and speed of agitation 350 rpm. Converted aluminum can reach 82%.Keywords: Aluminum sulphate, Dry process, Kaolin, Sulphuric acid, Stirred reactor